Problemas de Historiografia Helenística - Breno Battistin Sebastiani (Classica Digitalia: Humanitas Supplementum - Estudos Monográficos, 2019)
Some of the texts gathered in this book were produced for the international event "Hellenistic Historiography: new theoretical-methodological approaches", held at DLCV / FFLCH / USP and MAE / USP between September 15 and 16, 2016. Both the event and the book problematize by their formats, the very notion of "Hellenism" in which they are based: both take it in the broad chronological sense as proposed by Droysen in the Vorrede of 1836, that is, a period of antiquity which would extend approximately from the death of Alexander in 323 BC until the founding of Constantinople in 330 BC.